Pembangunan Aplikasi Penyambungan Kabel Fiber Optic Menggunakan Metode Fusion Berbasis Simulasi - Muhammad Ghaniy Hartanto; Winarno Sugeng; Rio Korio Utoro (Maranatha University Press, 2016)
Splicing of optical fibers have two methods i.e fusion splicing and mechanical splicing. Fusion splicing method is chosen because this method is gives permanent fusion. Fusion splicing is the act of combining two optical fiber end-to-end using heat parallel electrodes. The goal is to combine the two fibers together such that light passing through the fiber scattered or reflected back. Merging optical fiber using this method to connect Fusion Splicing can be done using a tool arc fusion splicer. Arc fusion splicer is a tool that is used to connect the optical fiber using parallel electrode rod smelting technology for accurate light reflection perfect. This study is to build simulation about how to splicing optical fibers using fusion splicing. Â Simulation program is chosen because of the price arc fusion splicer is very expensive ranging from millions rupiah in 2014, so this simulation media may be one visualization of the original tools of arc fusion splicer. The expected goal is to be able to know how to connect the fiber optic cable is good and rightÂ fiber optic cable by using simulation based on Internatonal standards ITU-T (International Telecommunication Union).Keywords: Fiber Optic, Fusion Splicing, Mechanical Splicing, Arc Fusion Splicer